Analysis of Influencing Factors of Speed Fluctuation of Oval Arc Tooth Line Cylindrical Gears - Huang Jiaming; Song Aiping; Yu Chenwei; Qiu Zhou (Jixie chuandong)
In order to ensure the normal working state of oval arc tooth line cylindrical gears under bad working conditions, reduce its vibration and noise, and improve its transmission characteristics, the transmission dynamic characteristics of oval arc tooth line cylindrical gear pairs are analyzed. Aiming at the analysis of transmission speed fluctuation of gear pairs under different radius of arc tooth lines, different tooth widths and different speeds, the kinematics and dynamics simulations of oval arc tooth line cylindrical gear pairs are carried out using the Adams software, and the influence rules of three different conditions on gear speed fluctuation are obtained, which provide help for the selection of geometric parameters and determination of processing parameters of involute oval arc tooth cylindrical gears.